Reasonability of God Inspection in Quran - Mohammad Hoossein Khavaninzadeh; Mahmood rasoli; Nematollah sadeghi (پژوهش نامه معارف قرآنی, 2016)
The issue of verifiability of God’s existence is one of the important subjects of studies in the realm of religion and new theology. In case of accepting it, the theory of demonstrability of God is justified. This paper aims to study the  various viewpoints  which tend to prove  the  existence of God (unreasonable and  determinate and implicit reasoning and indirect reasoning) and the end has shown predominate of those reasons which are implicit and  determinate attempting to prove the  Existence of God . In the other part of this extract, the importance and rational reasons of theology were mentioned through Quranic reasoning. Quranic verses in harmony with this result pertaining will be analyzed and stated.